An Egg Feeding Intervention Increased Protein Quantity and Quality Among Young Malawian Children. (29th May 2020) - Caswell, Bess; Arnold, Charles; Lutter, Chessa; Maleta, Kenneth; Stewart, Christine
Abstract: Objectives: Adequate protein quantity and quality are necessary for child health, growth and development, but may be lacking in complementary feeding diets with limited variety and few animal source foods. We assessed the impact of an egg feeding intervention on protein quality and quantity among rural Malawian children aged 9 to 15 months. Methods: We enrolled 660 children into a 6-month trial to test the effect of eggs on child growth. Children were randomly assigned to the egg group ( n = 331), who received one egg per day, or the control group ( n = 329). Dietary intake data were collected at 3-month midline (9–12 months old) and 6-month endline visits (12–15 months old) by 24-hour recall interview with the primary caregiver. Repeat recalls were collected in a subsample at each timepoint. Crude protein intakes were calculated using local recipe and food composition tables. Breast milk intake was estimated as the difference between the estimated energy requirement and energy intake from complementary diet. Protein intakes were adjusted using the Digestible Indispensible Amino Acid Score (DIAAS), which weighs crude amino acid intakes against amino acid requirements. Treatment group differences in DIAAS were tested with ANCOVA. Group differences in adjusted total protein intakes from complementary diet and breastfeeding were tested using the National Cancer Institute method for estimating usual mean intakes with bootstrap standard errors. Adequacy was assessed using World Health Organization protein requirements. Results: The egg intervention improved protein quality of the complementary feeding diet (DIAAS of 79 egg v 61 control at midline, 86 v 72 at endline, P < .0001). Inclusion of breast milk in the DIAAS increased mean scores in both groups; total protein quality remained higher in the egg group. Total quality-adjusted protein intakes were 15.4 ± 0.3 g (mean ± standard error) in the egg group v 12.7 ± 0.3 g in the control group at midline and 17.1 ± 0.3 g egg group v 14.6 ± 0.3 g control at endline ( P < .0001). Inadequacy of protein intake was lower in the egg group than the control group at midline (2% v 15%, P < 0.01) and very low in both groups at endline (<1% egg v 2% control, P > 0.05). Conclusions: The egg intervention increased quantity and quality of protein intakes among young Malawian children, though protein inadequacy was uncommon. Funding Sources: The Bill and Melinda Gates Foundation.